2002
DOI: 10.1007/s00455-001-0097-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of the Supraglottic and Super-supraglottic Swallowing Maneuvers in Stroke Patients with Dysphagia

Abstract: The prolonged voluntary closure of the glottis during the supraglottic and super-supraglottic swallowing techniques may create the Valsalva maneuver. The Valsalva maneuver has been associated with sudden cardiac death and cardiac arrhythmias. This study describes the effects of the supraglottic and super-supraglottic swallowing techniques on the cardiovascular system. Subjects included 23 patients from an acute inpatient rehabilitation hospital. Subject groups included recent stroke, dysphagia. and a history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 8 publications
0
24
0
1
Order By: Relevance
“…stroke, Alzheimer’s and Parkinson’s diseases). Dysphagia treatments often involve both exogenous and endogenous techniques (Chaudhuri et al, 2002; Logemann and Kahrilas, 1990; Pelletier and Lawless, 2003). Despite evidence that swallowing kinematics can be modified with different forms of input, the underlying neural substrates associated with these effects are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…stroke, Alzheimer’s and Parkinson’s diseases). Dysphagia treatments often involve both exogenous and endogenous techniques (Chaudhuri et al, 2002; Logemann and Kahrilas, 1990; Pelletier and Lawless, 2003). Despite evidence that swallowing kinematics can be modified with different forms of input, the underlying neural substrates associated with these effects are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Under conscious decision humans are able to swallow and stop a breathing cycle whenever required. In this way, to swallow with a large lung air volume, high lung elastic resistance, in association with vocal folds closure could reinforce the airway protective mechanism as proposed by supraglottic and super-supraglottic maneuvers (2,3,7) . Nevertheless, under subconscious control, humans do not swallow in association with deep inspiration.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Chaudhuri et al (2002) demonstrated that using these maneuvers in stroke patients resulted in arrhythmias that occurred within a treatment session, subsided within minutes of session end, and that did not occur during other activities. (51) Thus clinicians should be mindful of using these maneuvers in stroke patients especially in those with coexisting heart disease.…”
Section: Traditional Dysphagia Therapymentioning
confidence: 99%